The Impact of Growth Mindset Interventions on Student Achievement - Pong Krit; Ming Pong; Vicheka Rith; Suyitno Suyitno (Research Psychologie, Orientation et Conseil, 2025)
A student’s underlying beliefs about intelligence whether it is a fixed trait or can be developed (a “mindset”) is a powerful predictor of academic resilience and achievement. Fostering a growth mindset, the belief that intelligence is malleable, has been identified as a critical target for educational interventions aimed at improving student success. This study aimed to quantitatively evaluate the impact of a targeted, school-based growth mindset intervention on the academic achievement and perseverance of middle school students in a challenging subject. A quasi-experimental, pre-test/post-test study was conducted with 250 8th-grade students. The intervention group (n=125) participated in six workshops focused on neuroplasticity and growth mindset principles. The control group (n=125) received standard study skills training. Academic achievement was measured by mathematics grades and standardized test scores. The intervention group demonstrated a statistically significant improvement in their mathematics grades (p < .01) and reported higher levels of academic perseverance compared to the control group. The control group showed no significant change in either measure over the same period. Targeted, low-cost growth mindset interventions are an effective strategy for improving student academic achievement. Fostering the belief that intellectual abilities can be developed through effort is a powerful pedagogical tool for enhancing student success and resilience.